Nicaragua - Development Policy Review : Sustaining Broad-Based Growth - World Bank (Washington, DC, 2013)
This document reviews Nicaragua's development agenda from a growth perspective. That focus emerges from the country's Poverty Reduction Strategy Paper (PRSP), which traces the widespread poverty observed in Nicaragua, to the collapse of the 1980s, and considers a continued, broadly-based economic recovery as the best way to eliminate it. The focus on growth guides the review of policy developments in various economic, social, and infrastructure sectors. The Development Policy Review (DPR) has the objective of providing analytical underpinnings, both for the Government in developing and refining its growth strategy, and the Bank and other donors, in designing their assistance programs for Nicaragua. The macroeconomic program agreed with the International Monetary Fund (IMF) seeks to promote sustained growth, and poverty reduction in a stable manner, by connecting the country's large fiscal, and external imbalances, addressing key vulnerabilities, and removing long-standing barriers to growth. Key focal points of the program are measures to improve governance, and accountability in the public, private sectors, rein in sustainable government spending, raise the tax effort, and strengthen the banking sector. On the structural front, significant advances were made in 2002 in education and health, including strengthening of the public sector management, through an integrated financial management system, and other important reforms. However, key macroeconomic challenges outline the country's continuing dependence on a few primary commodity exports and aid, both of which have contributed significantly to the high level of economic volatility. A second issue concerns the sustainability of Nicaragua's macroeconomic framework, a weak spot in policymaking, deserving careful attention. To address shortcomings, the report suggests accompanying the Fiscal Transfers Law with additional measures, or legislation that 1) defines the spending responsibilities; 2) strengthens project planning and executing capacities of the weaker municipalities; and, 3) establishes appropriate accountability, and financial management mechanisms. In addition, the pension reform initiated in the mid-1990s, seeks to replace the current defined-benefit, pay-as-you-go system, by a defined-contribution system. The status of the pension reform is being reviewed, reassessing its fiscal costs with assistance form the Bank.